Experimental study of tensile strength for 3D printed specimens of HI-PLA polymer material on in-house tensile test machine - Pezer, Danijela; Vukas, Filip; Butir, Marin (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In the paper, a tensile test was performed on in-house made tensile test machine. The test was conducted on 3D printed test samples made according to the ISO 527-2 standard. The samples are made of HI-PLA (High Impact Polylactide) polymer material with pronounced resistance to impact toughness and it is closer, according to its characteristics, to ABS material. The test samples were printed by FDM additive technology with different layer thickness and material filling percentage, and a central composite test plan was carried out. The conducted experiment resulted in stress-strain diagrams for 11 states of the test samples, on the basis of which the tensile strength of the HI-PLA material was calculated. The obtained values ​​were compared with the tensile strength values ​​for ABS material.